Simultaneous orthogonal bipole mapping compared to conventional electrode configurations and impact on ablation strategies: results from a real world observational study. (24th May 2021) - Fiedler, L; Roithinger, F; Roca, I; Lorgat, F; Roux, A; Lacotte, J; Miller, A; Steven, D
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: 3D mapping systems are pivotal to identify low voltage areas and to define ablation strategies. In this context, high-density multipolar mapping catheters with varying electrode configurations are used for accurate myocardial substrate definition. High density mapping using a grid shaped catheter allows for use of simultaneous analysis of adjacent orthogonal bipolar signals that may assist in more accurate substrate characterization and ablation strategy decisions. Purpose: This was a prospective, multicenter observational study to characterize the utility of electroanatomical mapping with a high density grid-style mapping catheter (HD Grid) in subjects undergoing catheter ablation for persistent atrial fibrillation (PersAF) or ventricular tachycardia (VT) in real-world clinical settings. Methods: Mapping was performed with the HD Grid catheter to generate high-density maps of cardiac chambers in order to assess the potential influence of the simultaneous orthogonal bipole configuration on PersAF and VT ablation strategies. Differences in substrate identification between simultaneous orthogonal bipole configuration and standard along-the-spline electrode configuration, and potential effects on ablation strategies were investigated. Results: During the study period (January 2019 through April 2020), 367 subjects underwent catheter ablation for PersAF (N = 333, average age 64.1yr, 75% male) or VT (N = 34, average age = 64.3yr, 85.3% male). In total, 494 maps were generated to treat patients undergoing PersAF ablation and 57 to treat patients undergoing VT ablation. Compared to standard along-the-spline configuration, mapping with the simultaneous orthogonal bipole configuration showed differences in 57.8% (178/308) of maps generated, with the greatest difference noticed in surface area of low voltage (62.9%) and location of low voltage (55.6%). In comparisons performed live during the procedure (n = 50), simultaneous orthogonal bipole configuration assisted in identification of ablation targets in 70.0% of cases, changing the ablation strategy compared to that identified with along-the-spline configuration in 34.3%. In comparisons performed retrospectively after the procedure (n = 258), the ablation strategy identified with simultaneous orthogonal bipole configuration differed from along-the-spline configuration in 21.7% of maps. Even compared to a higher-density electrode configuration using all-bipoles rather than along-the-spline bipoles, simultaneous orthogonal bipole configuration identified differences in 57.1% of maps. Conclusion: The HD grid catheter combined with simultaneous orthogonal bipole configuration can define myocardial substrate more accurately compared to standard along-the-spline configuration. The difference in substrate identification has potential impact on ablation strategy. Further clinical trials are needed to elucidate the role of orthogonal bipole configuration mapping and improved ablation success rates.